Harmoni Spiritualitas dan Modernitas: Dinamika Pendidikan Agama Islam di Era Digital - Ulfa, Nur Henik Maria (Institut Agama Islam Sunan Giri Ponorogo, 2024)
slamic religious education is experiencing a critical period amidst modernity and technology due to the growing anti-Islam sentiment and the impact of terrorist attacks on a global scale. This article examines how Islamic religious education has been modified for the digital era in order to preserve religious identity and promote the fusion of modernity and spirituality. The literature review shows that Islamic religious education must change in order to remain effective and relevant in the information age. Islam is generally recognized as a religion that prioritizes harmony and tranquility, as evidenced by the development of advanced Islamic civilization. Elaborating on the fundamental idea of the harmonious relationship between modernity and spirituality, the importance of maintaining technology in the context of the information revolution is emphasized. The revitalization of Islamic religious education—especially through online platforms—is claimed to be one way to spread Islamic principles, encourage communication, and create a scientific community network. Islamic religious education aims to uphold the morals and character of the younger generation while navigating the complex dynamics of modernity and global challenges. This article concludes by highlighting the importance of reviving religious education as a means of innovation that supports religious identity in the context of technological advances and societal changes in the digital era.